Lakáshitelezés, állami támogatások - Cserné Endrődy Réka (2017)
The reason for choosing the topic of housing loans, state subsidies is on the one hand the fact that we built our family house this year. We took out a housing loan at Rábaközi Takarékszövetkezet (Rábaköz credit union), so I had the opportunity to familiarize with the relevant laws and government regulations, and we also requested a family benefit for setting up a home relating to our two children. Thereby I had the opportunity to familiarize with the process, content and structure of contract conclusion, as well as the relating declarations. On the other hand, I work with loans at my workplace, so most of experiences come from this field. The purpose of this thesis is to present in detail the current situation of loans and state subsidies in Hungary. I will build up the structure of loans from the very basics. I interpret residential loan types and the fundamental concepts relating to loans. I will cover state subsidies in detail, including the tax refund, the interest subsidy on setting up homes, and the family benefit for setting up a home. Practical aspects will also be presented, through Rábaközi Takarékszövetkezet. Based on my observations, the program on setting up new homes reached its purpose. The state has managed to stimulate the economy. It has created a vast number of new jobs, mainly in the construction business. There is a great demand for buying and building homes. Among families the highest demand is for subsidized housing loans, which causes a boom for credit institutions. Besides all these, I have been seeking to collect information on the downside as well. I have been trying to establish the actual benefits an average family receives in today’s booming economic climate. During my research I came to the conclusion that in the current economic climate it is not easy to create the housing conditions for young people. The state offers countless opportunities, however, finding the most adequate solution requires thorough consideration.